Synthesis of Tricyclic and Tetracyclic Lactone Derivatives of Thieno[2,3-b]pyrazine or Thieno[2,3-b]quinoline: Preliminary Antitumor and Antiparasitic Activity Evaluation - Martins, Maria F.; Ribeiro, Francisco; Borges, Ana; Calhelha, Ricardo C.; Santarém, Nuno; Cordeiro-da-Silva, Anabela; Queiroz, Maria-João R. P. (Molecules, 2025)
Tricyclic and tetracyclic lactone derivatives of thieno[2,3-b]pyrazine or thieno[2,3-b]quinoline, and 2H-pyrones were prepared using different methodologies. Pd/Cu-catalyzed Sonogashira coupling using Et3N as a base, of methyl 7-bromothieno[2,3-b]pyrazine-6-carboxylate and (het)arylalkynes to yield the Sonogashira ester products, gave also the corresponding tricyclic lactones as minor products. However, the major products did not cyclize with TFA. Tricyclic lactones were then obtained by a tandem one-pot Sonogashira coupling and 6-endo-dig lactonization of 7-bromothieno[2,3-b]pyrazine-6-carboxylic acid with (het)arylalkynes, in good yields. Halogenated tricyclic lactones were synthesized by halocyclization using CuX and NXS. Tetracyclic lactones were synthesized through a Rh(III)-catalyzed formal [4+2] cycloaddition, between thieno[2,3-b]quinoline-2-carboxylic acid and internal alkynes, triggered by C-H activation, with the carboxylic group acting as a directing group. Using the SRB assay, the antitumor activity of both Sonogashira products and lactones was evaluated across five human cancer cell lines (CaCo-2, MCF-7, AGS, HeLa, NCI-H460). The best-performing compound was a Sonogashira product showing a GI50 < 10 µM in all tumor cell lines and low toxicity in PLP2 cells. Additionally, antiparasitic testing against Trypanosoma brucei and Leishmania infantum revealed some compounds with IC50 < 11 µM, though some level of cytotoxicity was observed in THP-1—derived macrophages.